Case Study Of PT Bank Central Asia, TBK - Indonesia (BCA) - Effendi, Effendi (2006)
The ups and downs of the banking industry in Indonesia correspond directly to the policy environment and the business cycle. BCA, one of the largest private banks in Indonesia, coupled with its financial strength, has the potential to become an anchor bank.